SISTEM INFORMASI PENGELOLAAN KEUANGAN MENGGUNAKAN METODE CASH BASIS PADA DESA SUKOMULYO - Dwi Wulan Agustin; Dendy Kurniawan (Pusat Riset dan Inovasi Nasional, 2024)
The Sukomulyo Village Office is a government agency located at Jln. Raya No 01 Sukomulyo Kaliwungu Selatan Kendal Regency, Central Java. This current system records budget receipts as well as receipts from within the village and expenditure of funds every month. Transactions that occur in the treasury section are operational transactions for budget receipts and revenues from within the village as well as operational transactions for disbursement of Village expenditure funds. The village office has receipts and expenditures of funds every month. Revenue is divided into two, namely revenue from within the village and outside the village. From within the village, namely, village original income, village treasury land, village market, village hall rental, etc. From outside the village, namely, ADD (Village Budget) funds which are from weighing fund income, other legitimate village income, central government assistance, district assistance, provincial assistance, etc. Expenditures are also divided into two, namely direct expenditure and indirect expenditure. Direct expenditure, namely, village head's salary, village secretary's PLH salary, village head election costs, village meeting costs, indirect expenditure, namely, operational expenditure of LKMD (Village Community Activity Institute), expenditure on PKK activities, expenditure on youth organization activities, capital costs of LKD (Village Activity Institute) , assistance with Poskesdes activities, assistance with social activities.